Collagenase inhibition by water-pepper (Polygonum hydropiper L.) sprout extract - Tomoaki Kawaguchi; Kaori Nagata (Shahrekord University of Medical Sciences, 2019)
Introduction: Collagenase plays an important role in the degradation of dermal matrix proteins leading to wrinkle formation. The objectives of this study were to evaluate the inhibitory effect of water-pepper (Polygonum hydropiper L.) sprout extract on the activity of collagenase and to identify the inhibitory compounds.Methods: Collagenase inhibitory activity was measured by spectrophotometric assay. Activity-guided fractionation was performed using liquid-liquid extraction of water and n-butanol and Diaion HP-20 column chromatography, followed by high-performance liquid chromatography (HPLC) fraction collection.Results: A methanolic extract of water-pepper sprout inhibited collagenase activity in a concentration-dependent manner with an IC50 value of 156.7 μg/mL. Collagenase inhibitory activity (IC50 = 23.5 μg/mL) was found in 50% methanol eluate from the HP-20 column chromatography of the n-butanol soluble fraction. The active compound (IC50 = 1.9 μg/mL) in the eluate was isolated by HPLC and identified as quercetin-3-O-galactoside (hyperoside) from comparing retention time, UV-Vis absorption, and mass spectra with those of the standard. Lineweaver-Burk plots revealed that hyperoside was an uncompetitive inhibitor against collagenase. Hyperoside was also the most abundant flavonoid present in the methanolic extract.Conclusion: These results suggest that water-pepper sprouts could be beneficial as a natural source of collagenase inhibitor which might be used for the treatment of skin aging.